Psychological Tension in Some Individual Games for Students of the Third Stage in the Faculty of Physical Education and Sports Science - University of Al-Qadisiyah - Mohamed Abdulrahman Mohamed (Journal of Global Pharma Technology, 2016)
Today, the progress in physical education and mathematical science is clear and tangible in all sports activities, leading to higher achievement through the training process, and the introduction of all sciences to raise the level of skill performance. These sciences have a direct impact on the students' results; play an important role in achieving the desired objectives. They affect the level of students and may contribute to the implementation of technical and planning duties. Psychological stress is one of the most important psychological factors, which can be observed through the behavior of the individual in his responses to the new sports situations, in order to discourage the skillful performance of the lesson. Fencing, wrestling and gymnastics are one of the most popular games. These students from the possibilities of the skillful performance of what has been taught and these games differ from other sports in the size of sports skills, which is increasing with increasing importance, especially in the academic stages. The importance of research is to study the psychological tension among the students of the third stage in the Faculty of Physical Education and Sports Sciences who practice (dueling, wrestling and gymnastics) and compare them according to the game to know any game with a high degree of psychological tension. Through the poll of experts and specialists and the fact that researchers teaching at the college noticed, it appeared that the psychological preparation processes did not take the integrated dimension of the teachers and staff memory in the field of training, since these operations did not take sufficient quota as well as physical and skill preparation for the purpose of psychological tension control student who It reflected on the student's performance level. And to know the level of our students in the performance of the basic skills in (fencing, wrestling and gymnastics).Teachers do not treat the psychological side well during the training and the exam. It is necessary to study the side of psychological stress in the students in the third school stage to know the best material in this aspect. And compared the psychological stress of the three games in the third phase. The sample included (80) students from the Faculty of Physical Education and Sports Sciences / University of Al-Qadisiyah, which included three subjects, distributed (20) students for fencing material (20) ), A student from the Gymnasium for the academic year (2017 - 2018). The researchers used the statistical file (SPSS), which does not find the statistical analysis of the research. The researchers concluded that the students of wrestling and gymnastics subjects have the lowest proportion of students of fencing with psychological stress and recommended that students take into account the psychological stress of students in the performance of practical examinations.Keywords: Psychological tension, Individual games, Physical Education and Sports Science.